(untitled) (Journal of Nepal Chemical Society, 2021)
Quantification of iron in different pharmaceuticals can be performed by different analytical methods. In this study, a rapid, sensitive and simple spectrophotometric method was used for the determination of iron (II) in different iron tablets. A spectrophotometric method is based on the reaction of iron (II) with 1,10-phenanthroline to form an orange-red chelating complex in an acidic medium. The maximum absorbance of the chelating complex was measured at 510 nm. The Beer Lambert’s law was found to be obeyed in the range of 0.4-4.0 mg/L of iron (II). Out of ten samples analyzed, the observed amount of iron (II) in nine samples were range from 105 to 96 mg whereas in one sample it was observed only 81 mg per 100 mg of the labeled amount of iron(II) by the manufacturer. Thus the results obtained by the spectrophotometric method using 1,10-phenanthroline as a color developing agent were nearly equal to the claimed values of iron (II) in different iron tablets from manufacturing companies.